The impact of emotion regulation therapy on emotion differentiation in psychologically distressed caregivers of cancer patients. Issue 4 (4th July 2021) - Mikkelsen, Mai B.; Elkjær, Emma; Mennin, Douglas S.; Fresco, David M.; Zachariae, Robert; Applebaum, Allison; O'Toole, Mia S.
ABSTRACT: Background and objectives: Emotion differentiation is considered adaptive because differentiated emotional experiences are believed to promote access to the information that emotions carry, enabling context-appropriate emotion regulation. In the present study, secondary analyses from a recent randomized controlled trial (O'Toole et al., 2019) were conducted to investigate whether emotion differentiation can improve as a result of psychotherapy and whether improvements in emotion differentiation are associated with reduced distress. Design and methods: A total of 81 distressed caregivers of cancer patients were randomized to Emotion Regulation Therapy (ERT), an intervention aimed at improving emotion differentiation and facilitating healthy emotion regulation, or a waitlist condition. Emotion differentiation scores could be calculated for 54 caregivers. Results: Repeated measures ANOVAs revealed that ERT led to significant improvements in negative ( η 2 = 0.21, p = .012), but not positive emotion differentiation ( η 2 = <0.01, p = .973). Correlation analyses showed that improvements in negative emotion differentiation were not associated with changes in distress. Conclusions: The results suggest that negative emotion differentiation can improve as a result of psychotherapy. Further research is needed to clarify how improvements in emotion differentiation following therapeutic interventions relate to treatment outcomes such as distress. Trial registration: ClinicalTrials.gov identifier: NCT02322905 .